Local Ecological Knowledge and Biological Conservation: Post-normal Science as an Intercultural Field - Jorje Ignacio Zalles (Íconos)
From a natural sciences perspective, efforts directed at the conservation of biodiversity are based upon what is known as conservation biology. Given its epistemological assumptions, conservation biology faces obstacles in the incorporation of wisdom originating in local ecological knowledge, that which a local population has gained about the local environment which it is surrounded by and due to its direct contact with this local environment, instead of the result of a product of a positivist scientific inquiry. Post-normal science has emerged in recent decades as an alternative for public management that aims to complement the search for knowledge by means of empirical approaches through the inclusion of understandings based on the everyday experiences and the subjective interpretation of natural phenomena, transcending the compartmentalization associated with scientific traditions born out of modernity. This article discusses the integration of local ecological knowledge and conservation biology from the perspective of post normal science, illustrating different forms of intercultural communication that would make the requisite dialogue of knowledges possible.